Generation of human induced pluripotent stem cell lines from patients with a RYR2 gene variant c.14201A>G (p.Y4734C): Implications for idiopathic ventricular fibrillation and catecholaminergic polymorphic ventricular tachycardia - Celiker, Canan; Zelenak, Stefan; Lietava, Samuel; Pachernik, Jiri; Bebarova, Marketa; Zidkova, Jana; Novotný, Tomáš; Barta, Tomas (Stem cell research, 2024)
Human induced pluripotent stem cell (iPSC) lines were generated from peripheral blood mononuclear cells (PBMCs) isolated from two related patients diagnosed with either idiopathic ventricular fibrillation or catecholaminergic polymorphic ventricular tachycardia, carrying an unknown variant in the RYR2 gene, c.14201A>G (p.Y4734C) and one healthy related individual. Reprogramming was done using a commercially available Epi5 Reprogramming Kit. The pluripotency of the iPSC lines was verified by the expression of pluripotency markers and by their capacity to differentiate into all three embryonic germ layers in vitro. These iPSC lines are available for functional analysis and in vitro studies of RYR2 channelopathy.
Keywords: dospělí; Female; buněčné linie; Ryanodine Receptor Calcium Release Channel; Induced Pluripotent Stem Cells; Adult; Tachycardia, Ventricular; ženské pohlaví; katecholaminergní polymorfní komorová tachykardie; lidé; buněčná diferenciace; Polymorphic Catecholaminergic Ventricular Tachycardia; indukované pluripotentní kmenové buňky; fibrilace komor; Cell Line; Male; Ventricular Fibrillation; komorová tachykardie; Cell Differentiation; mužské pohlaví; ryanodinový receptor vápníkového kanálu; Humans